Physical demands on elite lead rugby union referees - Bester, C.; Coetzee, D.; Schall, R.; Blair, M. (International Journal of Performance Analysis in Sport, 2019)
The aim of this study was to determine the physical demands on elite rugby referees by measuring match duration and some key global positioning system (GPS) metrics such as distance covered, heart rate, speed and metabolic power and to assess whether physical demands changed during the course of the match (first half vs. second half). Physical profile data and GPS metrics were collected from 17 elite referees during 205 matches. Mean match duration was 98 min and distance covered was 6 826 m. Referees produced 5% more metabolic power during the first half of a match (mean: 6.2 W/kg) compared to the second half. Referees spent 27% of the time in the "work zone" (speed 4.1 m/s and above). During a match, referees spent 46.8% of the time below 80% HRmax. Mean numbers of high-speed accelerations, decelerations and sprints/surges were approximately 20% lower during the second half. Comparison of between-individual and within-individual variation of referee physical performance suggests that referees generally performed consistently. Factors such as referee experience and increased rates of substitution might contribute to the reduced power measures during the second half. The results from this investigation can contribute to the development of lead rugby referee-specific physical conditioning programmes.